EFEKTIFITAS LKPD BERBASIS PENDIDIKAN KARAKTER MENGGUNAKAN MODEL GUIDED DISCOVERY PADA MATERI GARIS DAN SUDUT DI KELAS VII SMP NEGERI 2 KOTA BENGKULU - Veliesa, Gyzka; Hanifah, Hanifah; Maulidiya, Della (JP2MS, 2021)
This study aimed to produce the Development of Student Worksheets Based On Character Education Using Guided Discovery Model on Line and Corner Material In Class VII SMPN 2 Bengkulu that is valid category. This research was a research development (Research and Devolopment) by modifying 4D Thiagarajan procedure into 3 phases namely define, design, and development phase consisting of effectiveness test. Effectiveness LKPD was tested on thirty three students in class VII G SMP Negeri 2 Kota Bengkulu even semester of academic year 2017/2018. This research instruments effectiveness sheet. The results showed that: The Development of Student Worksheets Based On Character Education Using Guided Discovery Model on Line and Corner Material In Class VII SMPN 2 Bengkulu City included in category effective on the basis of: 1) the response of learners consisting of 11 items of statement with average score 47.10 in very good category; 2) the activities of learners consisting of 11 items statement with an average score of 46.25 in very good category; 3) educator activity consisting of 10 items statement with average score 43,13 in very good category; and 4) learning outcomes of learners achieve classical mastery 84.85%.